2017
DOI: 10.1016/j.jaci.2016.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of immune development in urban preschoolers with recurrent wheeze and/or atopy

Abstract: Background Disadvantaged urban children have high rates of allergic diseases and wheezing, which are diseases associated with Type 2-biased immunity. Objective To determine whether environmental exposures in early life influence cytokine responses which affect the development of recurrent wheezing illnesses and allergic sensitization. Methods A birth cohort of 560 urban families was recruited from neighborhoods with high rates of poverty, and 467 (83%) children were followed until 3 years of age. Cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…, and this past year, several studies expanded our knowledge of the influence of early-life allergen exposure on asthma risk and demonstrated interactions between these indoor allergens and genetic polymorphisms. 49,[53][54][55][56] These gene-environment interactions could act through epigenetic or nonepigenetic mechanisms. In addition, studies demonstrated links between genetic signatures and asthma phenotypes related to steroid responsiveness, adult-onset asthma, and total IgE levels.…”
Section: Cellular Mechanisms In Asthmatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…, and this past year, several studies expanded our knowledge of the influence of early-life allergen exposure on asthma risk and demonstrated interactions between these indoor allergens and genetic polymorphisms. 49,[53][54][55][56] These gene-environment interactions could act through epigenetic or nonepigenetic mechanisms. In addition, studies demonstrated links between genetic signatures and asthma phenotypes related to steroid responsiveness, adult-onset asthma, and total IgE levels.…”
Section: Cellular Mechanisms In Asthmatic Patientsmentioning
confidence: 99%
“…The role played by the environment in shaping the development and exacerbation of asthma is examined as well (Fig 3). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] We conclude with a section on health literacy, a critical component for successfully treating asthma, and other related advances.…”
mentioning
confidence: 99%
“…3 A number of factors affect early-life immune responses, including season of birth, 57 sex, 8 maternal stress, 9 and allergen and microbial exposures (farms, dog, cockroach, and endotoxin) during pregnancy and early life. 7,10 Reduced IFN-γ responses in cord blood and early infancy have been linked to the risk of LRTIs and recurrent wheezing in multiple cohorts. 1114 Interestingly, early-life LRTIs are associated with a significant increase in mononuclear cell T H 1 and T H 2 responses in early life.…”
Section: Perinatal Risk Factorsmentioning
confidence: 99%
“…1114 Interestingly, early-life LRTIs are associated with a significant increase in mononuclear cell T H 1 and T H 2 responses in early life. 7,14 An exaggerated response of PBMCs to bacterial pathogens in infancy has also been associated with an increased risk of subsequent wheezing and asthma in the Copenhagen Prospective Studies on Asthma in Childhood (COPSAC) study. 15 Furthermore, a diminished regulatory T-cell response at birth has been identified as a risk factor for allergic sensitization and wheezing.…”
Section: Perinatal Risk Factorsmentioning
confidence: 99%
“…In comparison, allergic children show enhanced cytokine production at birth but this decreased over time so that by age 5, this hyper‐responsiveness to stimuli had declined and cytokine responses were reduced in comparison to similar aged non‐allergic children. A comprehensive study of immune development in urban preschool children determined that early life environmental exposures are vital in the stimulation of cytokine responses . Importantly, although cytokine production increased with age, these responses at birth were poorly predictive for later responses at aged 1 or 3.…”
Section: Development Of Immunity In Early Lifementioning
confidence: 99%